Disability and risk of school related injury. Issue 1 (3rd February 2004) - Ramirez, M; Peek-Asa, C; Kraus, J F
Abstract : Objective: Approximately six million children with disabilities attend school in the United States. Cognitive and physical limitations may compromise their ability to handle environmental hazards and hence increase their risk for injury. The objective of this study was to describe the epidemiology of school related injury among children enrolled in 17 special education schools in one large, urban school district. Design: Altogether 6769 schoolchildren with disabilities were followed up from 1994–98. Injury and population data were collected from pupil accident reports and existing school records. Associations were estimated through generalized estimating equations. Results: A total of 697 injuries were reported for a rate of 4.7/100 students per year. Children with multiple disabilities had a 70% increased odds of injury compared with the developmentally disabled (odds ratio (OR) 1.7, 95% confidence interval (CI) 1.3 to 2.3). The physically disabled (OR 1.4, 95% CI 1.0 to 1.9) had a modest increased odds of injury. Cuts, bruises, and abrasions composed almost three fourths of all injuries; almost half of these injuries were to the face. Falls (34%) and insults by other students (31%) were the most common external causes. More than a fourth of injuries were sports related, and 21% occurred on the playground/athletic field. Injury patterns differed across disabilities. Conclusions: Although limited to one school district, the population studied is the largest cohort thus far of schoolchildren with disabilities. With this large study base, potentially high risk groups were identified and circumstances of injury described. This information is imperative for developing and improving school based injury prevention measures.